Multi-Scape Interventions to Match Spatial Scales of Demand and Supply of Ecosystem Services - Laca, Emilio A. (Frontiers in Sustainable Food Systems, 2021)
The original focus on supply of ecosystem services is shifting towards matching supply and demand. This new focus underlines the need to consider not only the amount of ecosystem services but also their spatial and temporal distributions relative to demand. Ecosystem functions and services have characteristic or salient scales that are defined by the scales at which the producing organisms or communities exist and function. Provision of ecosystem services (ES) and functions can be managed optimally by controlling the spatio-temporal distribution of landscape and community components. A simple model represents distributions of ES as kernels centered at the location of interventions such as grassland restoration or establishment of nesting habitat for pollinators. Distribution kernels allow non-habitat patches to receive ecosystem services from species they cannot support. Simulations for three contrasting ES producing organisms (bumblebees, Northern Harriers and oak trees) show the effects of interacting distribution of interventions and demand for ES. More ES demand is met when the intervention is spread out in the landscape and demand is evenly distributed, particularly when the kernel radius is much larger than the minimum intervention required for the ES producing unit to be established. Because different functions have different reaches and saturation points, the level of ES demand met at any point in space can be modulated by controlling the spatial distribution of landscape components created by interventions. Different ES can be promoted by the same type and quantity of intervention by controlling the continuum of scales in the distribution of interventions. This work provides a conceptual and quantitative basis to consider the spatial design of interventions to match ES supply and demand.